1987
DOI: 10.1246/bcsj.60.877
|View full text |Cite
|
Sign up to set email alerts
|

A Solvent-Extraction Study of the Hydrolysis of Tracer Concentrations of Bismuth(III) in Chloride Solutions

Abstract: The backward solvent extraction with dithizone(H2dz)–CCl4 solutions was used to examine the chemical species of bismuth(III) in 1 mol dm−3 of a (H,Na)Cl solution. A tracer concentration of bismuth(III) (ca. 10−11 mol dm−3) was found to exist mainly in the form of [BiCl5]2−, [BiCl5(OH)]3−, [BiCl4(OH)]2−, and [BiCl3(OH)3]3− in the (H,Na)Cl solutions. The constants of the successive hydrolysis, β1, β2, and β3, were calculated by using the distribution data. The resulting logβ1, logβ2, and logβ3 values were 10.9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…S6 †). 25,26 Moreover, the acid concentration imparts pore regulations to the mesoporous shells. A relatively low growth speed at a higher acid concentration benets the formation of ordered mesoporous shells, thus resulting in well-organized nanocages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6 †). 25,26 Moreover, the acid concentration imparts pore regulations to the mesoporous shells. A relatively low growth speed at a higher acid concentration benets the formation of ordered mesoporous shells, thus resulting in well-organized nanocages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Their studies suggested the major existence of polynuclear Bi(III) species as a result of hydrolysis. On the other hand, Hataye et al [2] and Suganuma et al [3] studied the mononuclear species formed in more diluted concentrations ofbismuth(III)(ca. 10" 11 -10" 9 Μ, 1 Μ = 1 mol dm" 3 ) in 1.0 M(H,Na)C10 4 ,1.0 M(H,Na)N0 3 , and 1.0 Μ (H,Na)Cl solutions, based on a backward solvent extraction with a dithizone(H 2 dz)-CCl 4 solution.…”
Section: Introductionmentioning
confidence: 99%